2014
DOI: 10.1086/676868
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Algorithm to Preselect Patients to Be Assessed Individually in Point Prevalence Surveys for Hospital-Acquired Infections in Surgery

Abstract: In this pilot study, we evaluate an algorithm that uses predictive clinical and laboratory parameters to differentiate between patients with hospital-acquired infection (HAI) and patients without HAI. Seventy-four percent of the studied population of surgical patients could be reliably (negative predictive value of 98%) excluded from detailed assessment by the infection control practitioner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…[7][8][9][10] Automated monitoring, especially of SSIs, has therefore been attempted at a number of hospitals to address the disadvantages of manual HAI surveillance. [11][12][13][14][15][16][17] However, overestimation of HAI rates, the difficulty in differentiating between infection and colonization, and the failure to record late SSIs due to lack of post-discharge monitoring still have to be resolved. 18,19 The authors of this study have previously reported on an evaluation of an automated monitoring system called HAIR (Hospital-Acquired Infection Registry) based on a combination of laboratory and clinical data available as structured variables in various electronic hospital registries.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Automated monitoring, especially of SSIs, has therefore been attempted at a number of hospitals to address the disadvantages of manual HAI surveillance. [11][12][13][14][15][16][17] However, overestimation of HAI rates, the difficulty in differentiating between infection and colonization, and the failure to record late SSIs due to lack of post-discharge monitoring still have to be resolved. 18,19 The authors of this study have previously reported on an evaluation of an automated monitoring system called HAIR (Hospital-Acquired Infection Registry) based on a combination of laboratory and clinical data available as structured variables in various electronic hospital registries.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 55 risk factors were identified across the three types of surgical procedures from literature [15], [18][19][20][21][22][23][24][25][26][27][28]. Of the risk factors identified, ASA class, body mass index (BMI), Preoperative length of stay and diabetes were identified as general risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…The Erasmus MC University Medical Center in Rotterdam, the Netherlands (Erasmus MC), is the largest university medical hospital in the Netherlands with more than 1.300 beds. [21] We used the verified output from the infection control practitioners (ICP) for the SSI output variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations